More on realism, phenomenology, and causation, in reply to Cheng. (December 2022) - Rose, David
First, I agree with Cheng that the argument from illusions to indirect realism is controversial, especially as to what is meant by "realism, " "veridical, " and "sense data" and the background assumptions underlying them. I provide a finer specification of some of the sub-movements that were the specific concerns of my previous article, particularly phenomenology as it currently sees itself in perception research, and the relevance of illusions. Perception has turned out to be far more complex than traditional philosophy realized, as has been revealed by recent research in neuroscience and psychophysics. Lastly, I answer Cheng's question about the "causal exclusion argument" by suggesting it is obviated by the temporal substructure of metaphysical states, and I provide a detailed supporting case inSupplementary Material .